Survey of Inflammatory Biomarkers in Blood and Sputum in Pulmonary Tuberculosis Patients - James Perdinan Simanjuntak; Siti Sakdiah; Fardiah Tilawati Sitanggang; Eva Ayu Maharani (Jurnal Health Sains, 2023)
Tuberculosis (TB) is still a global health problem that exists today. Various efforts to reduce the number of TB patients have been carried out ranging from detection efforts to treatment and prevention efforts. Many studies have been conducted previously to look at the detection potential of laboratory diagnoses in finding new cases of tuberculosis. Likewise, efforts to detect prognosis in the laboratory to monitor the development of the condition of TB patients. The development of inflammatory conditions in TB patients is important to accelerate the healing process of these patients. Inflammatory marker tests have been widely performed on several types of laboratory test parameters. CRP and LDH are types of testing that have potential as markers of inflammatory development in TB patients. However, proven tests generally use blood specimens, which are commonly used in laboratory analysis for these parameters. Meanwhile, the current research theme has also been directed at the use of other types of specimens that can show inflammatory conditions experienced by a person. Saliva is known to have potential as another alternative specimen that can be used for such purposes. Saliva is easily obtained and does not require invasive techniques such as needle invocation, so it is considered to have more advantages if it can be proven as a laboratory test specimen that can provide information that is as good and accurate as blood or serum. This study aimed to assess the potential of saliva as an alternative specimen for laboratory analysis with the aim of markers in the assessment of prognosis of TB patients. CRP examination and LDH enzyme activity were chosen in this study of serum and saliva specimens of TB subjects and controls. From this study, it is expected to be shown that saliva can be used as an alternative specimen in laboratory analysis for inflammatory marker tests on both parameters. The results obtained showed that the measurement of LDH activity and and CRP levels in saliva observed in this study proved to have good potential in predicting the presence of inflammation and cell damage experienced by TB subjects. LDH test results have a strong relationship between serum and saliva as laboratory test materials, even salivary LDH levels are higher than serum. While CRP, although saliva showed low levels, the correlation test carried out still showed a strong relationship between the results of the two types of specimens.